Development and acceptability of a decision aid for anxiety disorder considering discontinuation of benzodiazepine anxiolytic - Aoki, Yumi; Takaesu, Yoshikazu; Inada, Ken; Yamada, Hiroki; Murao, Tomohiko; Kikuchi, Toshiaki; Takeshima, Masahiro; Tani, Masayuki; Mishima, Kazuo; Otsubo, Tempei (Frontiers in Psychiatry, 2023)
Aim To describe the development and acceptability of a decision aid (DA) for anxiety disorders considering discontinuation of benzodiazepine (BZD) anxiolytics, and if discontinuing, tapering with or without cognitive behavioral therapy (CBT) for anxiety. Methods We reviewed relevant literature describing anxiety disorders to identify treatment options. We also used the results of the systematic review and meta-analysis conducted previously to determine the related outcomes of two options: discontinuation of BZD anxiolytics by gradual tapering alone and discontinuation of BZD anxiolytics by gradual tapering with CBT. We then developed a prototype of DA following the International Patient Decision Aid Standards. A mixed methods survey was conducted to assess the acceptability among patients and healthcare providers. Results The prototype consisted of a description of anxiety disorders, options of continuing or discontinuing BZD anxiolytics (if discontinuing, the options of tapering anxiolytics with or without CBT), pros and cons of each option, and a value clarification exercise. Patients (n = 21) reported that the DA had acceptable language (86%), adequate information (81%), and well-balanced presentation (86%). Healthcare providers (n = 10) also provided favorable feedback. Conclusion We successfully developed a DA for anxiety disorders considering discontinuation of BZD anxiolytics, which was acceptable for stakeholders. The developed DA was designed to support patients and healthcare providers to make a decision together about whether to discontinue BZD anxiolytics.